(untitled) (LACCEI, 2024)
The study made it possible to measure the effectiveness of virtual university education strategies in times of Covid-19. Methodologically, a quantitative approach was used, whose design was non-experimental, of a descriptive type, which used the survey as a technique and the questionnaire as an instrument. The population was made up of higher-level students from the universities of the Piura Region in the year 2022. The findings conclude that: (1). With training for teachers, administrators and students, the use of technology becomes a competitive advantage. (2). The teacher plays a key role in strengthening virtual education, promoting teamwork, flexibility, and demand. (3). It is in the hands of the teacher to provide induction support to ensure a healthy academic environment. (4). Under the perception of the student, virtual education does comply with consolidating the competencies and objectives of the course. Finally, 56% of the students who participated in this study present a medium level of satisfaction with virtual university education and 44% a high or high level. These results ratify the good performance and the optimal level of adaptation that this group of universities located in the northern part of Peru have been incorporating.